Effectiveness of Early Cardiac Rehabilitation in Improving Quality of Life for Acute Coronary Syndrome Patients: A Systematic Review - Rany Novia Wardin; Elly Nurachmah; Sri Yona (Indonesian Journal of Global Health Research, 2024)
The provision of early cardiac rehabilitation intervention in patients with cardiovascular disease is necessary as it can accelerate recovery and determine the needs for the subsequent phases of cardiac rehabilitation. This study aims to identify the effectiveness of early cardiac rehabilitation on the quality of life of patients with acute coronary syndrome (ACS). The method used is a systematic review by searching articles in five journal databases: Clinical Key Nursing, ProQuest, PubMed, ScienceDirect, and Scopus. Article analysis used the PRISMA (Preferred Reporting Items for Systematic-Reviews and Meta-Analyses) method. The results of the study indicate that early cardiac rehabilitation significantly improves cardiac function, hemodynamic parameters, and patients mental health. Additionally, the use of innovative educational technologies, such as augmented reality and mobile applications, has been shown to enhance self-efficacy, exercise tolerance, and adherence to rehabilitation programs. Cardiac rehabilitation also provides additional benefits for patients with Diabetes Mellitus (DM) complications, improving cardiorespiratory function, exercise capacity, and quality of life. The conclusion from the ten analyzed articles suggests that comprehensive and structured early cardiac rehabilitation is effective in improving the quality of life of ACS patients and provides long-term benefits in the secondary prevention of cardiovascular diseases.